Internationalization and the evolution of corporate valuation - Gozzi, Juan Carlos; Levine, Ross; Schmukler, Sergio L. (Journal of Financial Economics, 2008)
By documenting the evolution of Tobin's q before, during, and after firms internationalize, this paper provides evidence on the bonding, segmentation, and market-timing theories of internationalization. We find that Tobin's q does not rise after internationalization, even relative to domestic firms. Instead, q rises significantly before and during the internationalization year, but then falls sharply in the following year, quickly relinquishing the increases of the previous years. In decomposing these dynamics, we find that market capitalization rises before internationalization and remains high, while corporate assets increase during internationalization. The evidence supports the theory that financial internationalization facilitates corporate expansion, but challenges the theory that internationalization produces an enduring effect on q by bonding firms to a better corporate governance system.